Andrey Stoyanov and Pancho Vladigerov at the beginning of the XX century (until 1944) - Shushulova-Pavlova, Milena (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Pancho Vladigerov‘s prominence and personality in the musical culture of Bulgaria is great. Until 1932, Vladigerov lived in Germany. He returned to Bulgaria after the Nazis came to power. For 40 years he taught composition and piano at the Sofia Academy of Music, which is bearing his name today. In my various studies of Andrey Stoyanov’s works I have come across materials about the relationship between Vladigerov and Stoyanov, which was not common, yet amicable enough. The three conversations quoted by me between these two great Bulgarians – two postal cards and one letter, are evidence of their professional communication, which was probably the reason for Pancho Vladigerov‘s establishment in Bulgaria and his professorship at the Music Academy.